Examination of nutrient leaching dynamics of Solidago virgaurea in Hévíz Lake and Hévíz canal - Simon, Szabina; Simon, Brigitta; Anda, Angéla (Acta Agraria Debreceniensis, 2021)
The different nitrogen and phosphorus elements are prime constituents of the ecosystem and can exert a major effect on aquatic species and the overall ecological cycle. During our investigation we examined the nutrient leaching dynamics in decomposing leaf litter (stem and leaf blades) of Solidago virgaurea. We chose four different sampling sites during the winter period with different water temperatures in the Hévíz Lake and Hévíz canal. The bottles containing the plant material and water were incubated at natural temperatures and the fluid was removed at particular times. Water parameters such as pH level, conductivity, nutrients (ammonium and phosphates) were measured. In the case of Solidago leaf, we obtained higher values ​​for all parameters compared to the stem ones.